An integrated view of bacterial resistance in the antibiotic era: efflux pumps biofilms and plasmids - Mohammed, Zahraa (Journal of Biomedicine and Biochemistry, 2025)
Antibiotic resistance is a widespread problem that reduces the effectiveness of antibiotics, leading the rise of multidrug resistance (MDR). Efflux pump, biofilm formation and plasmid based gene transfer together form the basis of co-adaptive mechanisms providing fleeting tolerance resistant overtime. Genes encoding efflux systems are alternative efflux-pumping systems that remove some antimicrobial agents, so that over extremely low intracellular concentrations are required for the bacterium to survive in the biofilm matrix.These, in turn, contribute to the structural and functional coherence of biofilms, which serve as protected niches favoring horizontal gene transfer and the propagation of plasmid-mediated resistance genes. In this review, we combine recent data from molecular and omics-based studies to demonstrate how these systems are co-regulated to control resistance in bacteria, with an emphasis on cross-talk between regulatory pathways including quorum-sensing, stress-response signalling and global transcriptional regulators. Insights into this interplay can pave the way for innovative therapeutic strategies, such as efflux pump inhibitors, biofilm dispersal agents and plasmid-curing strategies. Comprehensive knowledge of these interrelated processes may influence the development of future antimicrobial agents and their use, and may reduce the emergence of pan-resistant species of bacterial pathogens.